(untitled) (Fiep Bulletin - online, 2013)
This is an experience report from the training held in PRODUC - Initiation Sport, which is a project developed by the city of Duque de Caxias in partnership with the University of Rio Grande - UNIGRANRIO, and the Municipal Sports and Leisure. We conducted a study on the dimension of leisure sports, aiming to encourage children and teens when sports practice. Among the existing arrangements was chosen sport of Athletics to run the stage in question. For construction of the research it was decided to approach the dimensions of methodological Novikoff (2010), through a qualitative research the simple observation (GIL, 2009). The results showed that this was a sport unfamiliar, because the vast majority of students enrolled has never had contact with the Athletics. Therefore, we believe that this work can contribute to discussions and reflections of inserting the physical education professional in this area, working in the broadcast of sports through sports recreation, contributing to acts of promotion, health prevention, expanding the culture of body movement and talent discovery.